HUBUNGAN KUALITAS INFORMASI AKUN INSTAGRAM @COFFEEINESEEKER DENGAN PEMENUHAN KEBUTUHAN INFORMASI FOLLOWERS - Puspita, Reza Eka; Rizal, Edwin; Anwar, Rully Khairul (Pustabiblia: Journal of Library and Information Science, 2024)
This study discusses the relationship between information quality on the @coffeeineseeker Instagram account and the fulfillment of followers’ information needs. the purpose of this study is to determine whether there is a relationship between the quality of information on the @coffeeineseeker Instagram account and the fulfillment of followers’ information needs. measurement of information quality using information quality theory according to McLeod and Schell which consists of relevant, accuracy, timeliness, and completeness of information. The method used in this research is a quantitative method with a correlational approach. The sample used was 100 respondents selected using probability sampling with simple random sampling technique. Data collection techniques through online questionnaires, observations, interviews, and literature studies. This study uses the spearman rank correlation test technique. The results showed that there is a relationship between the information quality of the @coffeeineseeker Instagram account and the fulfillment of followers’ information needs. There is a relationship between relevance, accuracy, timeliness, and completeness of information with followers’ information needs. This means that the information provided by the @coffeeineseeker Instagram account meets the information quality indicators, so that it can fulfill followers’ information needs about café references.